A RARE OCCURRENCE OF UNILATERAL DUPLICATION OF WHARTON’S DUCT WITH THEIR INTRA-SUBLINGUAL GLANDULAR COURSE: A CADAVERIC REPORT - Ramalingam, Sudha; Somanath, Deepa (Journal of Morphological Sciences, 2019)
Anatomical variations regarding the salivary glands and their ducts have been observed in previous studies. But the occurrence of accessory submandibular gland duct is less common. In this study, we report a male cadaver with duplicated submandibular duct on the right side. The right upper submandibular duct (main duct) emerged from the anterior aspect of the deep part of the gland, ran its course forward, then pierced the posterior aspect of the sublingual gland and within the gland it ran forward and opened on the posterior aspect of sublingual papilla on the floor of mouth. The lower submandibular duct (accessory duct) also commenced from the anterior aspect of the deep part of the submandibular gland, ran forward just below and superficial to the upper duct and entered the anterior aspect of the sublingual gland and finally opened on the anterior aspect of sublingual papilla separately. Here, the embryological basis for the development of duplicated ducts and its clinical relevance is discussed. Key words : accessory submandibular duct, duplicated salivary duct, sialography, sialolith, Wharton’s duct